Ethnicity, Social Determinants of Health, and Pediatric Primary Care During the COVID-19 Pandemic - Pyone David; Sarah Fracci; Jennifer Wojtowicz; Erin McCune; Katyln Sullivan; Garry Sigman; Julie O'Keefe; Nadia K. Qureshi (SAGE Publishing, 2022)
This study assessed the relationship between ethnicity, social determinants of health (SDH), and measures of health outcomes for children during the COVID-19 pandemic. This retrospective study reviewed electronic medical records of 1234 in-person well child visits (WCVs for age <18 years) at a single academic primary care clinic in a Chicago suburb for the results of SDH screening in the domains of food, financial, and transportation insecurity. The association between ethnicity, unmet SDH domains, routine medical care delay, vaccine delays, and utilization of acute and emergency department (ED) visits were evaluated. Patients with unmet SDH were more likely to be non-White ( P  < .001), ≥3 years of age ( P  < .001) and have Medicaid coverage ( P  < .001). Unmet social needs were also associated with more acute visits ( P  < .001), ED visits ( P  < .001), and WCV delays ( P  < .001). The results suggest that the COVID-19 pandemic has disproportionately affected patients with unmet SDH in obtaining routine pediatric well child care.